Archaeogenetic insights into the demographic history of Late Neanderthals - Charoula M. Fotiadou; Jesper Borre Pedersen; Hélène Rougier; Mirjana Roksandic; Maria A. Spyrou; Kathrin Nägele; Ella Reiter; Hervé Bocherens; Andrew W. Kandel; Miriam N. Haidle; Timo P. Streicher; Nicholas J. Conard; et al. (Proceedings of the National Academy of Sciences, 2026)
The demographic history of Neanderthals is only partially understood. In Europe, some degree of genetic continuity has been shown from 120 thousand years ago (ka) onward despite the occurrence of multiple subsequent diversification events. While it has been proposed that a population turnover preceded the emergence of Late Neanderthals in Europe, the extent, timing, and geographic location of this event are currently unknown. Here, we report ten mitochondrial DNA sequences (mtDNAs) of Neanderthal individuals from six archaeological sites in Belgium, France, Germany and Serbia, and analyze them alongside 49 published mtDNAs. The integration of phylogenetic and molecular dating analyses with an extensive archaeological dataset enabled us to reconstruct temporal and spatial patterns in Neanderthal distribution. Remarkably, nearly all Late Neanderthal individuals across Europe belong to a single mtDNA lineage that diversified recently, confirming a large-scale genetic replacement. Our analyses date this diversification event to approximately 65 ka and suggest that it likely originated from a population refugium in southwestern France from which Neanderthals appear to have undergone a major range dispersal across Europe. In addition, we detect a sharp decline in the Neanderthal mtDNA effective population size beginning ~45 ka and reaching a minimum ~42 ka, shortly before their extinction. This study demonstrates that integrating molecular and archaeological datasets provides a more detailed understanding of the Late Neanderthal population’s history, and highlights the critical role of climate-driven refugia and subsequent range expansions in shaping the genetic landscape of Neanderthals through time.